A New Multiple Blind Signatures Using El-Gamal Scheme - Muthanna Abdulwahed Khudhair (Journal of Madenat Alelem University College, 2018)
This paper presents a new secure blind signature. In order to secure the blind signature, this scheme generates two blind signatures. Each of the blind signatures has its own blind factors. In addition, the author of the message encrypts the information sent to the signing author by an encryption key generated by El-Gamal cryptosystem, which is considered a strong cryptographic key. This key adds a secure and hidden layer to the message being signed. In addition, the author of the message binds an agreement factor for each type of message and a context that characterized the type of message signed. This method provides the most important properties for a secure blind signature.